2008
DOI: 10.1038/sj.bjc.6604242
|View full text |Cite
|
Sign up to set email alerts
|

CD44+CD24− prostate cells are early cancer progenitor/stem cells that provide a model for patients with poor prognosis

Abstract: Recent evidence supports the hypothesis that cancer stem cells are responsible for tumour initiation and formation. Using flow cytometry, we isolated a population of CD44 þ CD24 À prostate cells that display stem cell characteristics as well as gene expression patterns that predict overall survival in prostate cancer patients. CD44 þ CD24 À cells form colonies in soft agar and form tumours in NOD/SCID mice when as few as 100 cells are injected. Furthermore, CD44 þ CD24 À cells express genes known to be importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
353
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(375 citation statements)
references
References 25 publications
11
353
0
2
Order By: Relevance
“…These cancer-initiating cells have also been identified in the established androgen-dependent cell line LNCaP 43 and in androgen- independent prostate cancer cell lines DU145 43,44 and PC-3. 25,45 In this study, we showed that, in PC-3 cells, expression of CSC markers CD44 and CD133 was downregulated by c-T3 treatment (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…These cancer-initiating cells have also been identified in the established androgen-dependent cell line LNCaP 43 and in androgen- independent prostate cancer cell lines DU145 43,44 and PC-3. 25,45 In this study, we showed that, in PC-3 cells, expression of CSC markers CD44 and CD133 was downregulated by c-T3 treatment (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, such CD44 þ CD24 À cells from prostate and breast cancer cells exhibited increased tumor-initiating capacity compared with their PC in severe combined immunodeficiency mice. [29][30][31][32][33] The sorted CD44 þ CD24 À cells are hereafter referred to as CSCs. Collectively, our data suggest that both CSCs and spheres exhibited diverse stem cell-associated characteristics, consistent with previous reports.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, previous evidence from our laboratory showed that EphA2 drives melanoma cells toward a conversion of their mesenchymal style to an amoeboid-like behavior, finally leading to a successful lung and lymph node peritoneal metastasis (16). Several reports have acknowledged the CD44 high /CD24 low ratio as a reliable indicator of stemness in prostate and breast carcinoma cells (32,33). In this light, we analyzed the expression of these two markers in EphA2-silenced PC3 cells.…”
Section: Epha2-silenced Prostate Cancer Cells Lose Their Ability To Imentioning
confidence: 95%